Persepsi masyarakat terhadap kawasan tanpa rokok di terminal Dara - Zahratul Hayati; Yayi Suryo Prabandari; Trisasi Lestari (Berita Kedokteran Masyarakat (BKM), 2017)
Bima community perceptions on initiation of non-smoking area in Dara terminalPurposeThis study aimed to determine the passengers’ perceptions about the effort to authorize Dara terminal of Bima city as a non-smoking area.MethodsThis study was a qualitative research with a phenomenological approach. Data were collected by observation in August for 2 weeks and through in-depth interviews with 20 informants among terminal users. Data were analyzed using content analysis technique.ResultsTerminal users understand that: (1) smoking can cause serious illness and even can cause death, (2) the public are benefited from the terminal as a non-smoking area, because they can access the terminal without fear of the exposure, and (3) cooperation is needed with other parties to reduce the number of smokers in the terminal. Obstacles that may be present in this effort to authorize the non-smoking area are smoking habits in the terminal which are considered normal and traders who feel threatened because cigarette smoking is the goods that are often bought by smokers in the terminal. A non-smoking area is considered can be implemented if the regulation is realistic, well socialized to people, and the communities obey to the regulation.ConclusionsThe initiation of a non-smoking area in Dara terminal of Bima city can be accomplished if there is a policy of non-smoking areas, in cooperation with relevant parties and followed by a thorough socialization so that people who access the terminal can determine and adhere to the non-smoking area policies that will be formed.